Ionic liquid regioisomers: structure effect on the thermal and physical properties. (28th October 2014) - Watkins, John D.; Roth, Elliot A.; Lartey, Michael; Albenze, Erik; Zhong, Mingjiang; Luebke, David R.; Nulwala, Hunaid B.
Abstract : Effects of side group placement was studied on triazolium ionic liquids and how a minor change in alkyl group placement results in very different properties. Abstract : A systematic study was performed on two triazolium ionic liquid isomers which included examination of thermal, physical, and electrochemical properties. It was found that a minor change in structure significantly influences physical and thermal properties of ionic liquids.